2017
DOI: 10.1016/j.jval.2017.08.1002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acrylic Monofocal Intraocular Lenses (IOLS) on ND:YAG Laser Capsulotomy Rates: A Meta-Analysis

Abstract: A575Objectives: Cataract surgery is the most frequently performed surgical operation in the EU and Nd:YAG laser capsulotomy, a procedure to treat posterior capsular opacification (PCO), is the most commonly reported complication after cataract surgery. The aim of this study was to investigate the incidence of Nd:YAG laser capsulotomy reported in the literature for hydrophobic monofocal AcrySof® IOLs versus non-AcrySof monofocal acrylic IOLs (hydrophilic and hydrophobic). MethOds: Randomized controlled trials (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The effectiveness of hydrophobic acrylic and hydrophilic acrylic IOLs was compared in two recently conducted meta-analyses of RCTs, whereby the reported Nd:YAG capsulotomy rates were lower for the hydrophobic acrylic group [8, 13]. Furthermore, in a head-to-head meta-analysis, AcrySof IOLs were associated with a significantly lower risk of Nd:YAG capsulotomy compared to other acrylic IOLs [43]. Unlike an NMA, these meta-analyses included only direct evidence for their comparison.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of hydrophobic acrylic and hydrophilic acrylic IOLs was compared in two recently conducted meta-analyses of RCTs, whereby the reported Nd:YAG capsulotomy rates were lower for the hydrophobic acrylic group [8, 13]. Furthermore, in a head-to-head meta-analysis, AcrySof IOLs were associated with a significantly lower risk of Nd:YAG capsulotomy compared to other acrylic IOLs [43]. Unlike an NMA, these meta-analyses included only direct evidence for their comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Further to evidence from RCTs, similar results from observational research have been reported. In Ursell et al (2018), the authors assess AcrySof versus groups of other hydrophobic and hydrophilic IOLs, concluding that the risk of undergoing an Nd:YAG capsulotomy is significantly lower when AcrySof IOLs are used [43].…”
Section: Discussionmentioning
confidence: 99%